2017
DOI: 10.1038/s41598-017-14490-x
|View full text |Cite
|
Sign up to set email alerts
|

On the relevance of the alpha frequency oscillation’s small-world network architecture for cognitive flexibility

Abstract: Cognitive flexibility is a major requirement for successful behavior. nNeural oscillations in the alpha frequency band were repeatedly associated with cognitive flexibility in task-switching paradigms. Alpha frequencies are modulated by working memory load and are used to process information during task switching, however we do not know how this oscillatory network communication is modulated. In order to understand the mechanisms that drive cognitive flexibility, ERPs, oscillatory power and how the communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…It has been found that alpha frequency oscillations posses an important role in inhibitory control actions managing access of data of a cognition procedure and working memory [75][76][77]. Our findings show that several nodes within the gamma 1 band have an overall higher amount of closeness centrality during the imagined task in comparison to realized tasks.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…It has been found that alpha frequency oscillations posses an important role in inhibitory control actions managing access of data of a cognition procedure and working memory [75][76][77]. Our findings show that several nodes within the gamma 1 band have an overall higher amount of closeness centrality during the imagined task in comparison to realized tasks.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…This suggests that OCD patients, in contrast to controls, differentiate between the processing of repetitive (BI) and nonrepetitive (BASE) information. Well established findings suggest that the P1 reflects inhibitory, perceptual categorization processes needed to filter out relevant stimulus features in task‐relevant networks and to block information processing in potentially competing task‐irrelevant networks (Klimesch, ; Wolff, Zink, Stock, & Beste, ). The P1 reflects mechanisms regulating access to a knowledge system in which also previous task sets are stored (Klimesch, ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the Watts and Strogatz method to study small‐world networks (Watts & Strogatz, ). As done in previous studies, this method was applied to each single subject (Beste et al, ; Wolff, Zink, et al, ; Zink et al, ): Using this method, one starts from a one‐dimensional network, where each node in the network (in the current study, the EEG electrode) is only connected to its k nearest neighbors on either side, representing a “regular” network with randomness = 0, a ring lattice with N nodes of mean degree 2 k is created. Next, more connections (“edges”) are randomly chosen to another random node with increasing randomness ( > 0 ) .…”
Section: Methodsmentioning
confidence: 99%